Peningkatan Partisipasi Perempuan dalam Pemerintahan sebagai Upaya Tercapainya Affirmative Action - Supit, Advent Pesah Victoria; Nisa, Zakiya Ayu; Jabbar, Abdul (Universitas Negeri Semarang, 2024)
Since birth, humans have been attached to human rights as rights they have to be recognized and respected and aimed at realizing the human values given by God Almighty. Equality is a form of human rights, women and men have the same role in government. The government has established a policy for women's representation in government at a minimum of 30%. The real data in Kemiri Village is that women's involvement in government and village organizations has not yet reached 30%. Therefore, it is necessary to increase women's participation in Kemiri Village. The Kemiri Village UNNES KKN Team collaborates with youth youth organizations at the Gondang Satriyan for One Association (PEGASUS). The method used is the case study stage by searching for data and discussions with related parties, the second stage is outreach to youth organizations. As a result of this activity, women have an important role in government, with the privileges they have. The form of discussion carried out also allowed young people to practice expressing their opinions. With this outreach, it is hoped that it will be a step to increase women's involvement in government.